Kajian Literatur Standar Akuntansi dan Pedoman Pelaporan Keuangan Partai Politik di Indonesia - Sudrajat Martadinata; Arya Zulfikar Akbar; Tri Satriawansyah (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
This research is motivated by the importance of accountability and transparency in the financial governance of political parties in Indonesia, which is an important foundation for a healthy democracy, but there is still a significant gap between existing regulations and financial reporting practices. The purpose of this study is to identify and review various accounting standards and financial reporting guidelines that have been implemented or proposed for political parties in Indonesia, analyze the conformity between political party financial reporting practices and the principles of accountability and transparency in public financial governance, and identify challenges and gaps in the implementation of political party financial reporting standards based on findings from academic and policy literature. The research method involves in-depth analysis with a literature review scoping approach. The results of the study indicate that in political party financial reporting, there are SAK and SAP that are applied, transparency and accountability are needed in their management, and understanding the challenges and gaps in the implementation of political party financial reporting standards. In conclusion, to improve accountability and transparency, this study recommends the development of special accounting standards for political parties, strengthening transparent regulations and audit mechanisms, increasing independent supervision, and increasing awareness of accountability. By systematically addressing these challenges, political parties can improve their effectiveness as democratic entities and contribute to the progress of society as a whole